2010
DOI: 10.1007/s00380-009-1183-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of H1-receptor antagonists and left ventricular remodeling in patients on chronic hemodialysis

Abstract: Suppression of left ventricular (LV) remodeling secondary to heart failure seems critical to improve the prognosis of hemodialysis (HD) patients. This is a retrospective study on the relationship of an antiallergic drug and antihistamines with LV hypertrophy. A total of 149 patients (88 males and 61 females) were entered in the study. Mean age was 66.7 years and mean duration of dialysis 14.4 years. Twenty-three patients received oral treatment with an antiallergic drug or second-generation antihistamines, 3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In the long term, this compensatory response may become deleterious. In this setting, it is of importance to consider the potential role of new drugs interfering with the cardiomyocytes trophicity and left ventricular remodeling [33,34]. In this work, we report that astressin, a competitive antagonist of UCN, prevents the hypertrophic response of mature cardiomyocytes to UCN, as well as phosphorylation of GSK-3b and accumulation b-catenin.…”
Section: Discussionmentioning
confidence: 95%
“…In the long term, this compensatory response may become deleterious. In this setting, it is of importance to consider the potential role of new drugs interfering with the cardiomyocytes trophicity and left ventricular remodeling [33,34]. In this work, we report that astressin, a competitive antagonist of UCN, prevents the hypertrophic response of mature cardiomyocytes to UCN, as well as phosphorylation of GSK-3b and accumulation b-catenin.…”
Section: Discussionmentioning
confidence: 95%
“…SUA was measured [13] in subjects undergoing 4 months of aerobic training under the use of rhEpo. High-dose Epo and elevated SUA were considered [14] to be aggravating factors for the prognosis of heart failure hemodialysis (HD) patients. Increased oxidative stress (OS) and inflammation but similar SUA were found [15] in maintenance HD patients receiving Epo compared with healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells also had been noted to be associated with eccentric cardiac hypertrophy [22], which had an important impact on mortality in hemodialysis patients [23]. Omae et al showed that antihistamine therapy had a negative correlation with eccentric cardiac hypertrophy and could improve cardiovascular mortality in hemodialysis patients [24,25]. Therefore, the possible correlation between UP and cardiovascular mortality might be due to the release of histamine from mast cell, which could induce both pruritus and eccentric cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%